Imaging Low-Energy Ion Outflow in the Auroral Zone - Rowland, Douglas; Collier, Michael; Keller, John; Pfaff, Robert; Klenzing, Jeffrey; McLain, Jason; Clemmons, James; Hecht, James (Frontiers in Astronomy and Space Sciences, 2022)
The VISualizing Ion Outflow via Neutral atom imaging during a Substorm (VISIONS) sounding rocket mission investigated the factors leading to ion outflow during a geomagnetic substorm. In situ and remote sensing instrumentation provided complementary measurements that have been combined to yield an in-depth look at the phenomena associated with ion outflow. In particular the inclusion of instrumentation that provided high spatial and temporal resolution “images” of low-energy neutral atom (ENA) emissions from the nightside auroral zone following a substorm has led to new insights. The observed 50 eV ENAs were spatially structured, and strongly associated with regions of intense 630.0 nm auroral emissions. The ENAs in the auroral zone were predominantly up-going, consistent with either low-altitude acceleration with subsequent ENA-neutral scattering, or a “pressure cooker” scenario, with ions accelerated at higher altitudes and then reflected downwards to interact with the dense neutral atmosphere.